2012
DOI: 10.1176/appi.ajp.2011.11020289
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Stress-Induced and Cue-Induced Drug Craving: Influences of Sex and Cocaine Dependence

Abstract: Objective Although stress and drug cue exposure each increase drug craving and contribute to relapse in cocaine dependence, no previous research has directly examined the neural correlates of stress-induced and drug cue-induced craving in cocaine-dependent women and men relative to comparison subjects. Method Functional MRI was used to assess responses to individualized scripts for stress, drug/alcohol cue and neutral-relaxing-imagery conditions in 30 abstinent cocaine-dependent individuals (16 women, 14 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
217
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 265 publications
(253 citation statements)
references
References 64 publications
21
217
1
Order By: Relevance
“…This indicates that the videos increased urges to use drugs or gamble in content-and diagnostic groupspecific manners. However, gender-related main or interactive effects in self-reported cravings or urges were not observed, consistent with prior reports in CD (Li et al, 2005;Potenza et al, 2012). Indeed, despite a common stereotype that women may be more 'emotional' relative to men (eg, Timmers et al, 2003), similarities in self-reported emotion are common (see Barrett and Bliss-Moreau, 2009 for review).…”
Section: Subjective Responsessupporting
confidence: 80%
See 2 more Smart Citations
“…This indicates that the videos increased urges to use drugs or gamble in content-and diagnostic groupspecific manners. However, gender-related main or interactive effects in self-reported cravings or urges were not observed, consistent with prior reports in CD (Li et al, 2005;Potenza et al, 2012). Indeed, despite a common stereotype that women may be more 'emotional' relative to men (eg, Timmers et al, 2003), similarities in self-reported emotion are common (see Barrett and Bliss-Moreau, 2009 for review).…”
Section: Subjective Responsessupporting
confidence: 80%
“…Furthermore, we hypothesized that activity in regions previously implicated in drug cravings and gambling urges in CD and PG, including mPFC, ACC, striatum and insula, would be sensitive to diagnostic group and video type (eg, with CD participants showing greater activation in relation to cocaine videos). We also expected that some of these regions may show additional gender-related differences (ie, gender × diagnosis × video type interaction, as has been seen in cravings in CD; Potenza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent functional neuroimaging studies have sought to characterize the neural processing events that underlie attentional bias related to drug dependence as a means of understanding the mechanisms of relapse. Such study designs are distinct from those exploring the neural correlates of drug cue reactivity in the absence of assessing their cognitive bias properties by task interference effects (Kilts et al, 2001;Potenza et al, 2012). For nicotine-dependent individuals, the level of attentional bias for smoking-related cues was positively correlated with activation of the limbic, paralimbic, and occipital brain regions associated with emotional salience, memory recall, interoceptive states, and visual processing (Janes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of estrogens, and lower levels of progesterone, are associated with greater sensitivity to the euphorigenic properties of cocaine in women (Evans 2007). This increased sensitivity may contribute to why women, compared with men, start using cocaine regularly at a younger age (Chen and Kandel 2002), transition from use to abuse more quickly (McCance-Katz et al 1999), experience greater craving in response to drug-associated cues (Robbins et al 1999) and stress (Potenza et al 2012;Waldrop et al 2012), and exhibit more severe drug-seeking behavior upon relapse (Gallop et al 2007). In contrast, more women than men remain abstinent after treatment (Weiss et al 1997).…”
mentioning
confidence: 99%